Competency Development for Managing Patient with Mechanical Ventilators based on Caring - Nursalam, Nursalam; Sukartini, Tintin; Hidayah, Dewi Arini (International Journal of Psychosocial Rehabilitation, 2020)
Caring behavior needs to be applied to treat patients on a mechanical ventilator. Patients with a ventilator have special treatment according to their condition. The development of a caring-based nurse competency is necessary for nurses to provide holistic and competent care. This study aimed to develop management competencies for patients with ventilators based on caring. Research and development (R&D) with a descriptive approach was used. Purposive sampling was used to recruit 101 patients who met the inclusion criteria. The variables in this study were the competency of the management of the patients on mechanical ventilation. An observation sheet was used to gather the data and it was analyzed using descriptive analysis. There were 12 competencies of the nurses for the patients on mechanical ventilation, namely the prevention of Ventilator Acquired Pneumonia (VAP), respiratory physiotherapy, manual ventilation, treatment for restless pain and delirium, catheter care, promoting regular defecation, enteral feeding, parenteral nutrition, early mobilization, skincare, eye care, and communication. The module of competency for patient management based on caring was made according to a Focus Group Discussion (FGD), the study literature, and expert suggestion. The management competencies for patients on mechanical ventilators based on caring were VAP prevention, ventilator assessment, oral care, alarm handling, early mobilization, pain management, restlessness and delirium, and communication in patients on ventilators.